Treatment of large tracheal defects after resection: Laryngotracheal release and tracheal replacement. Issue 6 (December 2016) - Kirschbaum, Andreas; Teymoortash, Afshin; Suárez, Carlos; Shah, Jatin P.; Silver, Carl E.; Nixon, Iain; Rinaldo, Alessandra; Kowalski, Luiz P.; Robbins, K. Thomas; Ferlito, Alfio
Abstract: Objective: Resection with direct tracheal or laryngotracheal anastomosis is the standard procedure employed for treatment of benign stenosis or occasionally primary or secondary tracheal malignancy. Data sources: Literature review. Results: A tracheal anastomosis usually heals without complications provided that the ends being joined are adequately supplied with blood, an atraumatic suturing technique is used, and the anastomosis does not become infected. It is especially important that the anastomosis is not subjected to tension. Conclusion: Various techniques of laryngeal and tracheal release serve to reduce the tension on the anastomosis by mobilizing and reducing the distance between the two segments to be approximated. These techniques can be used in different combinations depending on situation encountered during surgery. In cases where more than 50% of the tracheal length must be excised, prosthetic replacements, autologous tissue transfer and allografts are required. All present various problems. The use of tissue-engineering techniques utilizing autologous stem cells has opened new perspectives for tracheal replacement. Such procedures are still in an experimental state.